An Overview of The Total Leukocyte Count in Pulmonary Tuberculosis Patients at RSUD Gambiran Kediri City - Fitri, Devi Nor; Savitri, Lisa; Krissanjaya, Rochmad; Kasimo, Elfred Rinaldo (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
The leukocyte count examination in tuberculosis infection serves to monitor the inflammation caused by Mycobacterium tuberculosis. An increasing leukocyte count can lead to complications such as pleuritis. The purpose of this study was to determine the total leukocyte count of pulmonary tuberculosis patients at RSUD Gambiran, Kediri City, based on gender and age. This research was a descriptive retrospective study. Data analysis was conducted using Microsoft Excel and presented in the form of tables and diagrams. The results of this study showed that pulmonary tuberculosis infection was more prevalent in males, with 26 individuals (62%) affected. In terms of age groups, the highest infection rate was in the 21-60 years age range, with 30 individuals (71%) affected. As for leukocyte count elevation (leukocytosis), it was more commonly observed in males with a count of 14.57 ÂµL. In terms of age groups, leukocytosis was frequently observed in the 21-60 years age range, with a count of 48.66 ÂµL. Out of the 42 samples, 19 individuals had a normal leukocyte count, while the remaining 23 individuals experienced leukocytosis. From the results of the study, it can be concluded that not all pulmonary tuberculosis patients experience leukocytosis; some patients maintain a normal leukocyte count.